2022
DOI: 10.1186/s12866-022-02686-9
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of 16S rRNA microbial data identified alterations of the gut microbiota in COVID-19 patients during the acute and recovery phases

Abstract: Background Dozens of studies have demonstrated gut dysbiosis in COVID-19 patients during the acute and recovery phases. However, a consensus on the specific COVID-19 associated bacteria is missing. In this study, we performed a meta-analysis to explore whether robust and reproducible alterations in the gut microbiota of COVID-19 patients exist across different populations. Methods A systematic review was conducted for studies published prior to May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 79 publications
4
26
0
2
Order By: Relevance
“…COVID-19 patients exhibited an enrichment of opportunistic pathogenic species including Bacteroides , Corynebacterium , Enterocloster , Enterococcus , Flavonifractor , Parabacteroides and Streptococcus compared with healthy controls. The abundance of anti-inflammatory butyrate-producing bacteria (e.g., Dialister , Faecalibacterium , Lachnospira , Megasphaera , Prevotella , Roseburia and Ruminococcus ) was reduced in COVID-19 patients ( 21 ). COVID-19 patients showed an imbalanced metabolism characterized by enhanced protein metabolism and suppressed carbohydrate-oriented catabolism, which might impel putrefactive gut microbiota dysbiosis in COVID-19 patients ( 19 ).…”
Section: Dynamic Alterations Of Gut Microbiota During Sars-cov-2 Infe...mentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 patients exhibited an enrichment of opportunistic pathogenic species including Bacteroides , Corynebacterium , Enterocloster , Enterococcus , Flavonifractor , Parabacteroides and Streptococcus compared with healthy controls. The abundance of anti-inflammatory butyrate-producing bacteria (e.g., Dialister , Faecalibacterium , Lachnospira , Megasphaera , Prevotella , Roseburia and Ruminococcus ) was reduced in COVID-19 patients ( 21 ). COVID-19 patients showed an imbalanced metabolism characterized by enhanced protein metabolism and suppressed carbohydrate-oriented catabolism, which might impel putrefactive gut microbiota dysbiosis in COVID-19 patients ( 19 ).…”
Section: Dynamic Alterations Of Gut Microbiota During Sars-cov-2 Infe...mentioning
confidence: 99%
“…↑Blautia, Lactobacillus, RuminococcusPositively correlate with proinflammatory cytokines IFN-g, IL-2, IL-4, IL-6, IL-8, IL-10 and TNF-a Magnify inflammation (35)(Continued)producing bacteria (e.g., Dialister, Faecalibacterium, Lachnospira, Megasphaera, Prevotella, Roseburia and Ruminococcus) was reduced in COVID-19 patients(21). COVID-19…”
mentioning
confidence: 99%
“…Since the introduction of the revolutionary method of bacterial characterization by Pace et al 26 , 16S rRNA-based characterization of bacterial species has been universally accepted as an accurate method for bacterial identi cation 27 . 16S rRNA metagenomic analysis has provided an objective tool to explore bacterial diversity and composition under a wide variety of clinical scenarios, in which 16S rRNA amplicon with SMS analysis was widely adopted for economic affordability and rapid microbial detection strategy 28 .To date, the use of 16S ribosomal RNA (rRNA) metagenomic analysis to study GM changes in the clinical setting have demonstrated the capability to analyze associations between GM changes and colorectal diseases 28 , COVID-19 infections 29 , prosthetic joint infections 30 , chronic wound infections after wisdom tooth extraction 31 , detection of postoperative infection sources 32 , and the potential to in uence SSI outcomes in colorectal surgery 14 . In this study, the 16S rRNA amplicon with SMS analysis was utilized to verify gut GM changes in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies over the course of the COVID-19 pandemic have revealed that the infection impacts the composition of the gut microbiome. A recent systematic review found that gut bacterial diversity was decreased in both patients with acute COVID-19 and those who have recovered from COVID-19, coupled with a decreased abundance of butyrate producers and increases in taxa with proinflammatory properties ( 35 ). This gut perturbation continued into the recovery phase after the resolution of an initial infection, suggesting that it may persist and could conceivably contribute, at least in part, to PASC in some individuals.…”
Section: Chronic Dysbiosis Of the Gut Microbiomementioning
confidence: 99%